1996
DOI: 10.1007/s002619900006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with sarcomatous change: characteristic findings of two-phased incremental CT

Abstract: The appearance of HCCSC on CT is that of an irregularly demarcated intrahepatic mass with delayed or prolonged peripheral enhancement, frequently with intrahepatic metastases and lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
7
30
0
Order By: Relevance
“…These results agree with those from previous studies in which peritumoral parenchymal enhancement or tumorous arterioportal shunt was associated with microvascular invasion (16,17,34). The rim enhancement pattern has been also suggested to indicate rapid progression, poor differentiation, and worse prognosis (22,25,35), possibly by reflecting the absence of a capsule, infiltrative growth, and the presence of microvascular invasion as well as rapid growth with central necrosis.…”
Section: Discussionsupporting
confidence: 83%
“…These results agree with those from previous studies in which peritumoral parenchymal enhancement or tumorous arterioportal shunt was associated with microvascular invasion (16,17,34). The rim enhancement pattern has been also suggested to indicate rapid progression, poor differentiation, and worse prognosis (22,25,35), possibly by reflecting the absence of a capsule, infiltrative growth, and the presence of microvascular invasion as well as rapid growth with central necrosis.…”
Section: Discussionsupporting
confidence: 83%
“…Sarcomatous HCC is an aggressive variant of HCC with an incidence of 3.9-9.4%, with either a sarcomatous change in part of the HCC or coexistence of a sarcoma and HCC [13]. Histologically, sarcomatoid HCC consists of very poorly differentiated cells that grow rapidly, resulting in central necrosis or hemorrhage due to inadequate blood supply.…”
Section: Sarcomatoid Hccmentioning
confidence: 99%
“…No capsule, intratumoral fat, or central scar is present. On cross-sectional images, sarcomatoid HCC shows peripheral enhancement with an unenhanced central portion that correlates to viable cancerous tissue with fibrous stroma in the periphery and central necrosis of the tumor, respectively [13] (Fig. 3).…”
Section: Sarcomatoid Hccmentioning
confidence: 99%
“…In the present case, the sarcomatoid changes were speculated to be induced by anti-HCC treatment, including radiofrequency ablation (RFA), percutaneous ethanol injection and transarterial chemoembolization, resulting in the degeneration, necrosis and regeneration of tumor cells (7,8). However, previous studies have reported cases with no history of prior therapy (8,9). The CT findings of sarcomatoid HCC have been reported to include irregularly demarcated intrahepatic masses with delayed prolonged peripheral enhancement (10).…”
Section: A B C Dmentioning
confidence: 70%